Tokyo xatirliri (2017)
Dieser Blog ist eine Webseite einer Uigurin in Tokio. Auf dieser Kategorie dieses Blogs werden Beiträge über die Kindererziehung in der Familie, die überwiegend aus dem Japanischen ins Uigurische übersetzt worden sind, veröffentlicht. Darüber hinaus enthalten viele Beiträge in diesem Blog Musikaudios, die Musik und Songs vieler Kulturen zum Ausdruck bringen. - This blog is a website of a Uyghur woman in Tokyo. In this category of this blog you will find articles about raising children in the family, most of which have been translated from Japanese into Uyghur. In addition, many posts in this blog contain music audio that expresses the music and songs of many cultures.